(untitled) (International Journal of Food and Nutritional Sciences, 2023)
Due to modernization, industrialization, Hinduism, Islamilisation, Christianization, and culturelization many normal and abnormal changes have occurred in their life. With the changes in cultures, influence of different religion the problems of social economical, cultural, religious, linguistic, health related arose in the life of Tribes. And significant changes have taken place in their life. Some tribe like Munda and Ho celebrate easter festival rather than their own. They are distributed in a group of christian and nonchristian. Due to the pessimistic atmosphere, folksongs of Adivasi in Chota Nagpur area express the meaning that our life is meaningless lets united for robbing.today Adivasi have no interest in their traditional dances. Holy dance and a dance of festival became pale. An adivasi with dual flute or a girl dancing with lezim is rarely seen. Internet, mobile and T.V. channels have also made equally bad effect among their traditional life. Dresses, lifestyle, celebration of festivals, and means of entertainment have changed.